A novel role for interferon regulatory factor 1 (IRF1) in regulation of bone metabolism. Issue 8 (20th June 2014) - Salem, Sandra; Gao, Chan; Li, Ailian; Wang, Huifen; Nguyen‐Yamamoto, Loan; Goltzman, David; Henderson, Janet E.; Gros, Philippe
Abstract Increased risk of bone fractures is observed in patients with chronic inflammatory conditions, such as inflammatory bowel disease and rheumatoid arthritis. Members of the Interferon Response Factor family of transcriptional regulators, IRF1 and IRF8, have been identified as genetic risk factors for several chronic inflammatory and autoimmune diseases. We have investigated a potential role for the Irf1 gene in bone metabolism. Here, we report that Irf1−/−mutant mice show altered bone morphology in association with altered trabecular bone architecture and increased cortical thickness and cellularity. Ex vivo studies on cells derived from bone marrow stimulated with Rank ligand revealed an increase in size and resorptive activity of tartrate‐resistant acid‐positive cells from Irf1−/− mutant mice compared with wild‐type control mice. Irf1 deficiency was also associated with decreased proliferation of bone marrow‐derived osteoblast precursors ex vivo, concomitant with increased mineralization activity compared with control cells. We show that Irf1 plays a role in bone metabolism and suggest that Irf1 regulates the maturation and activity of osteoclasts and osteoblasts. The altered bone phenotype of Irf1−/− mutants is strikingly similar to that of Stat1−/− mice, suggesting that the two interacting proteins play a critical enabling role in the common regulation of these two cell lineages.